Beetles : text and photographs - Watts, Barrie (London : Franklin Watts, 1989)
Part of a series which shows in close-up colour photographs and simple text how to care for small creatures, this book shows how to find, house, feed, care for and observe beetles. All the animals are easy to find in gardens, parks and open spaces.
Includes index.
Keywords: Beetles as pets -- Juvenile literature; Beetles -- Collection and preservation - -- Juvenile literature